Hubungan Konsumsi Makanan Kariogenik Dan Kebiasaan Menggosok Gigi Dengan Timbulnya Karies Gigi Pada Anak Usia 4-6 Tahun - FEBRI ENDRA BUDI SETYAWAN; PERTIWI FEBRIANA CHANDRAWATI; NATALIA MULYADI (Universitas Hang Tuah, 2018)
ABSTRACT The initial factor of the dental caries initiator is cariogenic food. In previous research states there is a relationship between eating patterns and the habit of brushing teeth with dental caries prevalence. This study aims to determine the relationship between the consumption of cariogenic foods and the habit of brushing teeth with the onset of dental caries disease in children aged 4-6 years in kindergarten Tunas Mekar at village Mlajah Bangkalan District. The research method is Descriptive Observational Analytic with Cross Sectional approach. The population in this study is all children aged 4-6 in the village Mlajah Bangkalan District. Samples taken by a total of 68 children using Total Sampling technique. Primary data obtained from observation and questionnaire, processed using Chi-Square test statistic and Discriminant test with degree of significance (α) = 0,05. The result showed that 49 children (84,5%) had dental caries on cariogenic food consumption ≥3x daily with habit of brushing teeth <2x a day. On the results of the Contingency Coefficient test obtained the value of r = 0.61 with a significance value in the Discriminant test. The conclusion of this study is a relationship between the consumption of cariogenic foods and the habit of brushing teeth with the dental caries at the time of children 4-6 years in TK Tunas Mekar, Mlajah village, Bangkalan District. The habit of giving cariogenic food which is more meaningful to make teeth compared to the eyes of brushing teeth